The The Role of Job Satisfaction Mediation in the Relationship between Compensation and Organizational Commitment in Security Outsourcing PT XYZ - Tiara Wigunastika; Hesty Prima Rini; Ayundha Evanthi (PT Larva Wijaya Penerbit, 2025)
This study aims to examine the effect of compensation on organizational commitment with job satisfaction as a mediating variable. A quantitative method was used to obtain objective empirical data, with respondents as many as 51 outsourced employees (security) at PT XYZ. Data collection was carried out through a questionnaire, then analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results showed that compensation has a positive and significant influence on organizational commitment. In addition, job satisfaction was shown to significantly mediate the relationship between compensation and organizational commitment. This suggests that adequate compensation can increase job satisfaction, which in turn strengthens commitment to the organization. These findings emphasize that companies need to pay attention to the quality of compensation and working conditions to maintain loyal and productive employees.